Sociology in our times - Kendall, Diana Elizabeth (Cengage Learning, 2017)
A social issue or application opens each chapter in this book, and many examples are carried on throughout. It incorporates recent research and diverse theoretical viewpoints including the feminist theory. This best-selling text will help you learn sociology and how it applies to a socially and globally changing world. Chapters open with a "Sociology and Everyday Life" box that highlights such relevant topics as bullying and social media abuse, digital-age methods to increase school attendance, food trucks and the spread of culture, modern slavery, and weight bias. These opening vignettes mirror the richness and complexity of society and establish themes that are carried throughout chapters to provide you with a framework for learning the material. The author's vivid, inviting writing style; eye for compelling current examples; thorough presentation of sociological theory and contemporary perspectives such as feminism and postmodernism; and emphasis on trying out what you're learning will engage you and show you sociology's relevance to your life